2020
DOI: 10.35975/apic.v24i3.1282
|View full text |Cite
|
Sign up to set email alerts
|

Operative site irrigation with povidone-iodine solution in spinal surgery for surgical site infection prevention: Can it be used safety?

Abstract: Povidone-iodine (PVI) is an effective disinfection solution for surgical wounds. However, there is some reports of its adverse effects on wound healing and bone reunion. Here, we evaluate the efficacy and safety of PVI irrigation in the prevention of surgical site infection in spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Reasons for exclusion after full-text review are listed in eTable 1 in Supplement 1. We included 41 RCTs in our systematic review and 37 RCTs in the network meta-analysis, due to lack of events in all arms in 4 studies . The study characteristics of the RCTs included in the systematic review are listed in eTable 2 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons for exclusion after full-text review are listed in eTable 1 in Supplement 1. We included 41 RCTs in our systematic review and 37 RCTs in the network meta-analysis, due to lack of events in all arms in 4 studies . The study characteristics of the RCTs included in the systematic review are listed in eTable 2 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…All but 2 studies described the antibiotic solutions to be aqueous. All antiseptic solutions studied were aqueous, with 18 RCTs investigating iodine solutions ranging from 0.1% to 10% in concentration. Other antiseptics used were polyhexanide, chlorhexidine, hydrogen peroxide, and electrolyzed strongly acidic aqueous solution .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Sigari et al reported on 936 spinal fusion surgery patients who were randomized to receive irrigation with either 3% PVP-I solution followed by normal saline for a maximum of two minutes (study group) or normal (control group). They did not find significant decreases in deep and superficial infections when analyzed individually, but did report the overall infection rate (deep + superficial) was reduced in the PVP-I group (4.8% to 1.1%, p = 0.032) [17].…”
Section: Povidone-iodinementioning
confidence: 91%